2011
DOI: 10.1007/s11896-011-9086-y
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Comprehensibility of a Canadian Police Caution on the Right to Silence

Abstract: Modifications to a Canadian police caution on the right to silence were made in an attempt to increase its comprehensibility. University participants were asked to imagine themselves in an arrest and interrogation situation in which they were either innocent or guilty. It was hypothesized that participants who received the modified caution would score significantly higher on measures of comprehension than those who received the standard caution. Results indicated that comprehension was significantly higher amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 49 publications
(49 reference statements)
4
15
0
Order By: Relevance
“…These findings are also consistent with previous tests of how well youths and adults comprehend the legal rights contained in police cautions and warnings (e.g., Davis, Fitzsimmons, & Moore, 2011;Eastwood & Snook, 2009;Grisso, 1981;McLachlan et al, 2011). Our exploratory test of youth comprehension of a youth waiver form, which had a medium level of complexity relative to other waiver forms, showed that the participants understood less than half of the rights contained in that waiver form.…”
Section: Results the Average Percentage Comprehension For The Final supporting
confidence: 90%
See 1 more Smart Citation
“…These findings are also consistent with previous tests of how well youths and adults comprehend the legal rights contained in police cautions and warnings (e.g., Davis, Fitzsimmons, & Moore, 2011;Eastwood & Snook, 2009;Grisso, 1981;McLachlan et al, 2011). Our exploratory test of youth comprehension of a youth waiver form, which had a medium level of complexity relative to other waiver forms, showed that the participants understood less than half of the rights contained in that waiver form.…”
Section: Results the Average Percentage Comprehension For The Final supporting
confidence: 90%
“…Our exploratory test of youth comprehension of a youth waiver form, which had a medium level of complexity relative to other waiver forms, showed that the participants understood less than half of the rights contained in that waiver form. These findings are also consistent with previous tests of how well youths and adults comprehend the legal rights contained in police cautions and warnings (e.g., Davis, Fitzsimmons, & Moore, 2011; Eastwood & Snook, 2009; Grisso, 1981; McLachlan et al, 2011). In general, the observed low level of comprehension begs the question of whether youths facing police interrogations are receiving an adequate level of protection.…”
Section: The Current Studysupporting
confidence: 90%
“…In addition, it is likely that many of the instances where rights were waived were invalid because the person waiving the rights simply did not understand what those rights were, and according to case law, the resulting statements could be ruled inadmissible in court (Marin 2004). To rectify this problem and improve the administration of justice in Canada, more effort must be taken to ensure police cautions are comprehensible to those for whom they are ostensibly designed (see Eastwood and Snook 2012;Davis, Fitzsimmons, and Moore 2011 for recent advances in this area). Further research is also needed to identify more directly the reasons for the lack of caution comprehension, given the inability of cognitive measures to account for the low comprehension levels.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, found that by first reducing the grade level required to comprehend an adult police caution (e.g., reducing grammatical complexity, removing difficult words) and then adding features to boost the clarity of the caution (i.e., providing instructions regarding the nature of the information to come, repeating important information multiple times, outlining the rights in a list format), comprehension levels increased by approximately 40%. A follow-up study using a mock police interview situation showed that the gains in comprehension largely hold up under more ecologically valid situations (Snook, Luther, Eastwood, Collins, & Evans, 2014; also see Davis, Fitzsimmons, & Moore, 2011).…”
Section: Introductionmentioning
confidence: 99%